PERANCANGAN QOS MANAJEMEN BANDWIDTHMENGGUNAKAN MIKROTIK METODE HTB (Information Technology and Telematics, 2015)
AbstractThe internet in the world of work develops very rapidly. PT. Intech Anugrah Indonesia using internet in activities daily work. In supporting activity need a stable connectivity. To solve a problem connectivity needs bandwidth manajement required to divide quota as need. Aplication of Quality Of Services an each client existing help maintaint the quality of the bandwidth. Mikrotik Router Board use for the implementation of the bandwidth management with the Hirarchical Token Bucket method. Key Word : Manajement Bandwidth, QOS, HTB